Retention of Volatile Components of Durian Fruit Lather during processing and Storage - Jaswir, Irwandi; Che Man, Yaakob; Selamat, Jinap; Ahmad, Faujan; Hiroshi, Sugisawa (Wiley Periodicals Inc., 2008)
A study was conducted to identify the volatile constituents of durian(Durio zibethinus Murr.) of clone D24 and to determine the retention of volatile components of durian fruit leather during processing and storage.Thirty-eight volatile compounds were identified in the fresh durian flesh, of which 11 were esters, 10 alcohols, six carboxylic acids, six sulphurous (S) and nitrogenous (N) compounds and five hydrocarbons. Processed durian fruit leather retained most of the aroma components of fresh durian fruit. During storage, the relative proportion of acids in the product increased, esters,alcohols and aldehydes decreased, while hydrocarbons and phenolic and S and N compounds fluctuated.